A clinical-epidemiological study of facial dermatoses in women - Spandana Reddy, Nallamilli; Upadhyaya, Janardhan A.; Prasad, Col. G K (ScienceRise: Medical Science, 2022)
The face is the most prominent part of the body. Facial blemishes and disorders directly reflect a person’s physical appearance, cosmesis and self-image. They may contribute to dysmorphism and even lead to depression in susceptible individuals, especially women. Early identification and management of facial skin disorders are therefore important. The aim: To study the clinical pattern and epidemiological determinants of facial dermatoses among females above 10 years. Methods: This cross-sectional study was conducted among female patients with facial dermatoses, with informed consent, at a rural tertiary hospital for 18 months. Results: A total of 500 patients were enrolled. The majority were in the 4th and 5th decades. Pigmentary dermatoses were highest, melasma predominating. Immunobullous dermatoses formed the smallest group. Occupation-wise, the majority were agricultural labourers. Many dermatoses, especially melasma, were related to occupation and lifestyle with photo-aggravation, cosmetics use and stress. Conclusion: This study assessed the pattern of facial dermatoses among the female clientele of this institution. Hyperpigmentary dermatoses, especially melasma, emerged as the most common dermatosis for which treatment was sought